Hubungan Antara Pengetahuan dan Sikap Remaja Dengan Tindakan Seks Pranikah pada Siswa Kelas XI Di SMK Negeri 2 Manado - Mangando, Elcya Natalia S.; Lampus, Benedictus S.; Siagian, Iyone E.T.; Kandou, Grace D.; Pandelaki, A.J.; Kaunang, Wulan P.J. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Adolescent is defined as a period of transition from childhood to adulthood. Adolescent age limit according to theWorld Health Organization (WHO) is 12 to 24 years. Problems that often experienced by adolescents today are issuessurrounding sexuality, especially premarital sex. Some studies show that 20 years ago, adolescents that approvedpremarital sex are around 1.2% - 9.6%, and then 10 years later rose to above 10% and 5 years later that percentagerose to 17%. Act of premarital sex is determined by the knowledge and attitudes held by adolescents. The purpose ofthis study was to analyze the relationship between adolescents knowledge and attitudes with premarital sex acts ofsecond grade senior high school students in SMK Negeri 2 Manado.This research is an analytical cross-sectional studiesdesign. Samples in this research are 82 respondents teens who have match the criteria. From the overall 82 adolescentrespondents show that most adolescent are well knowledge with the percentage of 52.4%, the attitude is dominatedwith positive attitude with a percentage of 54.9%, and the acts is dominated with good acts that is 61.0%. Chi-Square Test results indicate that there is significant relationship between knowledge and premarital sex acts (p =0.000) and no significant relationship between attitudes to premarital sex acts (p = 0.000). Overview of theknowledge, attitudes, and premarital sex acts of second grade senior high school students in SMK Negeri 2 Manadoobtained good. There is a relationship between knowledge of adolescents with premarital sex acts. There is a relationshipbetween attitudes with premarital sex acts. Conclusion : Overview of the knowledge, attitudes, and premaritalsex acts of second grade senior high school students in SMK Negeri 2 Manado obtained good. There is a relationshipbetween knowledge of adolescents with premarital sex acts. There is a relationship between attitudes with premaritalsex acts.Keywords: Knowledge, Attitudes, Acts, Premarital Sex, Adolescent